2018
DOI: 10.1016/j.celrep.2018.06.037
|View full text |Cite
|
Sign up to set email alerts
|

A Neural Circuit Underlying the Generation of Hot Flushes

Abstract: Hot flushes are a sudden feeling of warmth commonly associated with the decline of gonadal hormones at menopause. Neurons in the arcuate nucleus of the hypothalamus that express kisspeptin and neurokinin B (Kiss1 neurons) are candidates for mediating hot flushes because they are negatively regulated by sex hormones. We used a combination of genetic and viral technologies in mice to demonstrate that artificial activation of Kiss1 neurons evokes a heat-dissipation response resulting in vasodilation (flushing) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
110
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(120 citation statements)
references
References 40 publications
(49 reference statements)
2
110
1
1
Order By: Relevance
“…Cre:Cre is a Kiss1 KO as characterized elsewhere (Padilla et al, 2018). Kiss1 gene 297 was also confirmed undetectable from POA and MBH tissue (Supplement Figure 1).…”
Section: A Kiss1mentioning
confidence: 53%
See 2 more Smart Citations
“…Cre:Cre is a Kiss1 KO as characterized elsewhere (Padilla et al, 2018). Kiss1 gene 297 was also confirmed undetectable from POA and MBH tissue (Supplement Figure 1).…”
Section: A Kiss1mentioning
confidence: 53%
“…Cre:GFP knock-in mouse (version 2) was generated from C57Bl/6 blastocysts and 295 verified at the University of Washington (Padilla et al, 2018). The homozygous version of this 296…”
Section: A Kiss1mentioning
confidence: 99%
See 1 more Smart Citation
“…An important health consequence of the altered NKB signaling in postmenopausal women is the dysregulation of the heat dissipation center which seems to play a critical role in the pathogenesis of hot flushes [29]. In accordance with this concept, recent studies of mice have shown that the artificial activation of arcuate nucleus KP neurons evokes a heat-dissipation response which can be sensitized by ovariectomy [30]. Within this volume, Modi and Dhillo provide a review of the growing evidence supporting antagonism of the NKB receptor (NK3R) as a potential new treatment for menopausal hot flushes [31].…”
Section: Menopausal Alterationsmentioning
confidence: 89%
“…[1][2][3][4][5][6][7][8] Recently, however, it has been suggested that central kisspeptin signaling plays a broader role by coordinating the onset of puberty with metabolic parameters, such as nutrient sensing. [9][10][11][12][13] Here, we will discuss an additional and unexpected emerging role of Kiss1 ARC neurons in controlling whole-body skeletal homeostasis, highlighting recent studies that link both central and peripheral kisspeptin signaling to bone density and outlining important questions to be answered in this developing field (►Fig. 1).…”
mentioning
confidence: 99%